2017
DOI: 10.1016/j.vacuum.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification of indium implanted glassy carbon by thermal annealing and SHI irradiation

Abstract: The structural changes, migration behaviour of indium (In) implanted into glassy carbon (GC) and the effect of annealing on radiation damage introduced by ion implantation have been investigated. The GC substrates were implanted with 360 keV indium ions to a fluence of 2.0×10 16 ions/cm 2 at room temperature (RT) and 350 °C. The RT implanted samples were isochronally annealed in vacuum between 200 and 1000 °C for 1 hour. The 350 °C implanted GC substrates were irradiated 167 MeV with Xe 26+ ions at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
5
19
0
Order By: Relevance
“…A key property for a nuclear waste storage material is low diffusivity for the radioactive materials. Although there had been a few reports of diffusion of fission product elements in glassy carbon [17][18][19][21][22][23][24][25][26], this is the prime reason for this study, i.e. to determine the diffusivity of the radiological important fission product, strontium, in glassy carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key property for a nuclear waste storage material is low diffusivity for the radioactive materials. Although there had been a few reports of diffusion of fission product elements in glassy carbon [17][18][19][21][22][23][24][25][26], this is the prime reason for this study, i.e. to determine the diffusivity of the radiological important fission product, strontium, in glassy carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Two key factors for a material to be used in the nuclear industry are radiation hardness and diffusion properties. The radiation resistance of glassy carbon is largely unexplored with some Raman studies, see [12][13][14][15][16][17][18][19] and also with thermal conductivity measurements [20]. A key property for a nuclear waste storage material is low diffusivity for the radioactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has high thermal stability and does not transform into graphite even at high temperatures up to 3273 K [10,11]. Glassy carbon possesses physical, chemical and mechanical properties which make it very promising for technological applications [12]. These properties include moderate hardness, resistance to corrosion and wear, high chemical inertness [13], impermeability to gases and liquids [14].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of glassy carbon enumerated above have drawn the attention of many researchers to study its performance improvement by ion implantation. Notable studies on ion species implanted in glassy carbon include Co [19], Cd [11], In [12] and Cs [20]. The results of these studies showed that the diffusion patterns of the implanted ions were not into the bulk, but rather towards the surface of the glassy carbon damaged by ion implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on radiation resistance of beryllium and its oxide to neutron radiation originate in the middle sixties of the XX century [16,17]. At the same time, most data on radiation resistance cannot be compared with each other due to variety of sample types (single crystals, polycrystals, samples with different impurities), which is related to obtaining methods as well as to difference in operating parameters of nuclear reactors [18][19][20]. In the course of previously conducted studies, a procedure was developed for comparing different types of radiation, which is based on measuring changes in structural parameters, defect concentration in the structure and magnitude of atom displacements from lattice sites [21][22][23].…”
Section: Introductionmentioning
confidence: 99%